Vozes da estética na era das conexões: sobre corpo, consumo e emagrecimento - Brum, Luana Martins de (2016)
This thesis aimed to understand how the consumption practices related to the body and weight loss are experienced in women’s everyday life, in the Digital Age. Therefore, we carried out 2 studies: “Body, beauty and women: reflections about the body cult in the digital age” and “Fat body and slim body in the Digital Age: analyzing logical narratives on a weight loss blog. On the first study, it was made a reflection based on articles surveyed on LILACS and SciELO database, related to the research’s object (body, beauty and women). Applying content analysis three axes were created: a) studies on body’s representations, b) studies with women or women and men over 18 years old, and c) studies on goods consumption/habits related to the body cult, like diets and exercises. On the second study, we research testimonies regarding the experience of women that went through the weight loss process posted in a blog. The assumptions of the Critical Social Psychology and the narrative analysis of Patrick Charaudeau supported the analysis. As results, we found out that people don’t consume only goods or habits to achieve the thin body, but the thin body can be consumed itself, and the weight loss don’t get restricted to body modification only, going further, involving a new way to relate to your own self, others and the world.